The Influence of the Choice of Raw Materials on the Strength Characteristics in the Production of Ceramic Bricks in the Fergana Region - D.O., Son; S.S., Zakirov (RA Journal of Applied Research, 2021)
This article examines the effect of raw materials on ceramic bricks, as well as how raw materials change depending on storage conditions and storage duration. As you know, the quality of the finished product directly depends on the raw materials. A chemical analysis of raw materials of ceramic bricks was carried out in different fields of the Fergana region.